Pengobatan Tradisional Suku Sasak: Studi Kasus Pengobatan di Makam Keramat Yok Dasan Lekong, Lombok Timur, NTB - Aini, Riska; Hamdi, Saipul; Kusuma, Nila; Nasrullah, Arif (Religion, Culture, and State Journal, 2021)
This study aims to explore one of the traditional medicine traditions of the Sasak people in a sacred tomb of Yok in Dasan Lekong, Sukamulia, East Lombok. This traditional medicine has been running for a long time and continues to be maintained by the local communities until now, the Sasak people come on pilgrimages to treat sick family members. They believe that by bathing and following the ritual prayers at the tomb they can recover from illness. Therefore, this study specifically aims to understand the history of the emergence of Yok’s sacred tomb as a place of treatment, and the treatment procession carried out at Yok’s tomb. The complexity of the methods and processes in this treatment directs this research to understand the symbolic meaning of the offerings or the media used in the treatment and the reasons why the Sasak people still maintain the tradition of traditional medicine at the Yok sacred tomb. This research was conducted for one year using a qualitative method with a phenomenological approach. Determination of informants in this study using snowball sampling. The data collection techniques used observation-participation techniques, interviews, documentation, and also triangulation to cross check over all the data. The data analysis in this study used the social construction theory of Peter L. Berger and Tomas Luckman, and Herbert Blumer's theory of Symbolic Intractionism.